A Narrative Review of Binge Eating and Addictive Behaviors: Shared Associations with Seasonality and Personality Factors - Davis, Caroline (Frontiers in Psychiatry, 2013)
Binge eating disorder (BED) and seasonal affective disorder (SAD) were first described as clinically-relevant conditions in very close temporal proximity a few decades ago. Both disorders have a higher prevalence rate in woman than in men, are characterized by a high proneness-to-stress and manifest heightened responsiveness to high-calorie, hyper-palatable foods. In recent years, a compelling body of evidence suggests that foods high in sugar and fat have the potential to alter brain reward circuitry in a manner similar to that seen when addictive drugs like alcohol and heroin are consumed in excess. These findings have led to suggestions that some cases of compulsive overeating may be understood as an addiction to sweet, fatty, and salty foods. In this paper, it is proposed that high seasonality is a risk factor for binge eating, especially in those characterized by anxious and impulsive personality traits – associations that could only occur in an environment with a superfluity of, and easy access to, rich and tasty foods. Given the well-established links between binge eating and addiction disorders (22-24 for reviews), it is also suggested that seasonality, together with the same high-risk psychological profile, exacerbates the likelihood of engaging in a broad range of addictive behaviors. Data from a community sample (n=412) of adults tested these models using linear regression procedures. Results confirmed that symptoms of binge eating and other addictive behaviors were significantly inter-correlated, and that seasonality, gender, and addictive personality traits were strong statistical predictors of the variance in binge-eating scores. Seasonality and addictive personality traits also accounted for a significant proportion of the variance in the measure of addictive behaviors. Conclusions are discussed in the context of brain reward mechanisms, motivational alternations in response to chronic over-consumption, and their relevance for the treatment of excess